Uji Preklinis fraksi etil asetat daun jaloh (Salix tetrasperma Roxb) sebagai antiplasmadium secara in vitro - Nuzul Asmilia; Sugito Sugito; Amalia Sutriana (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2011)
The aim of the present study was to find out the in vitro activity of ethyl acetate fraction of willow leaves (Salix tetrasperma Roxb) on Plasmodium folcifarum (P. falciparum) growth.